2004
DOI: 10.1046/j.1365-2958.2003.03911.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of NleA, a non‐LEE‐encoded type III translocated virulence factor of enterohaemorrhagic Escherichia coli O157:H7

Abstract: Summary EnterohaemorrhagicEscherichia coli (EHEC) O157:H7 uses a specialized protein translocation apparatus, the type III secretion system (TTSS), to deliver bacterial effector proteins into host cells. These effectors interfere with host cytoskeletal pathways and signalling cascades to facilitate bacterial survival and replication and promote disease. The genes encoding the TTSS and all known type III secreted effectors in EHEC are localized in a single pathogenicity island on the bacterial chromosome known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
239
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(244 citation statements)
references
References 61 publications
2
239
1
2
Order By: Relevance
“…The ligation served as template in a PCR with primers 159 and 162 with the resulting 1.8-kb product being cloned into SacI/KpnI-digested pRE112, generating pNT256. pNT256 was conjugated into EPEC ⌬sepD, followed by the isolation and genotypic verification of ⌬sepD⌬nleA strains, as previously described (37). Similarly, a pRE112-based espZ deletion construct was created using primer pairs EPespZ(1) (GCGGTACCTGCT-TGTCGAGCAACGAGGCG) and ⌬EPespZ(R) (CCGCTAGCG-GATTAGCGATGAAATATGCC) and ⌬EPespZ(F) (GCGCTA-GCTGGTAATACTGCACCAGAAGG) and EPespZ(2) (CCGA-GCTCGAGTATCTTTGTATATTGACTC), followed by the isolation of ⌬espZ mutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligation served as template in a PCR with primers 159 and 162 with the resulting 1.8-kb product being cloned into SacI/KpnI-digested pRE112, generating pNT256. pNT256 was conjugated into EPEC ⌬sepD, followed by the isolation and genotypic verification of ⌬sepD⌬nleA strains, as previously described (37). Similarly, a pRE112-based espZ deletion construct was created using primer pairs EPespZ(1) (GCGGTACCTGCT-TGTCGAGCAACGAGGCG) and ⌬EPespZ(R) (CCGCTAGCG-GATTAGCGATGAAATATGCC) and ⌬EPespZ(F) (GCGCTA-GCTGGTAATACTGCACCAGAAGG) and EPespZ(2) (CCGA-GCTCGAGTATCTTTGTATATTGACTC), followed by the isolation of ⌬espZ mutants.…”
Section: Methodsmentioning
confidence: 99%
“…Infected HeLa monolayers were washed with phosphate-buffered saline, followed by fixation with paraformaldehyde (2.5%, v/v). The samples were processed for immunofluorescence microscopy as previously described (37). Monoclonal antibodies were used to stain fixed samples: anti-FLAG (1:2000) (Sigma), anti-Tir (1:500), and anti-PY (1:500) clone 4G10 (Upstate Biotechnology, Inc.), followed by extensive washing and staining with secondary antibodies (Alexa 488-or 568-conjugated anti-mouse (Molecular Probes), 1:400).…”
Section: Methodsmentioning
confidence: 99%
“…Five translocated effectors are encoded by LEE: Tir/EspE [35,88], Map [87], EspF [109], EspG [45] and EspH [169]. Two effectors are encoded outside the LEE by lambdoid prophages: Cif [104] and NleA/EspI [62,118]. Blast analysis revealed that homologues of NleA/EspI are encoded by an Stx1-converting phage in EHEC of serotype O84:H4 (unpublished results) or by the phage coding for Cif [104].…”
Section: The Locus For Enterocyte Effacementmentioning
confidence: 99%
“…Although much of the in vivo work on A/E pathogens has focused on the virulence roles of secreted proteins, others have attempted to determine tissue localization of effectors such as Tir (Deng et al 2003), in an effort to uncover function. Infection of mice with C. rodentium mutants confirms a critical role in colonization and virulence of the LEE-encoded effectors Tir, EspB, and EspZ, as well as the non-LEE-encoded effectors NleA and NleB (Newman et al 1999;Deng et al 2003Deng et al , 2004Gruenheid et al 2004;Mundy et al 2004;Kelly et al 2006), whereas others are thought to contribute collectively (Dean and Kenny 2009). Mice were orally infected with C. rodentium and colonic tissues were harvested and subjected to immunofluorescent staining at 6 days postinfection.…”
Section: In Vivo Infection Modelsmentioning
confidence: 99%